Diversity genotyping of Indian coffee (Coffea arabica L.) germplasm accessions by using SRAP markers. Issue 3 (4th May 2019) - Jingade, Pavankumar; Huded, Arun Kumar; Kosaraju, Bharathi; Mishra, Manoj Kumar
ABSTRACT: Coffea arabica L. is the only cultivated tetraploid species in the genus Coffea and it contributes more than 61% to the total world coffee production. Arabica produces superior beverage quality compared to robusta coffee but is susceptible to a number of pests and diseases. Improved varieties of arabica coupled with durable disease resistance can be achieved by incorporating novel sources of genetic variation from diverse germplasm sources. Assessment of genetic diversity within the germplasm pool is a prerequisite for estimating its true breeding potential. In the present study, 42 world germplasm accession of arabica were screened with co-dominant sequence-related amplified polymorphism (SRAP) markers. Twenty-one SRAP combinations amplified a total of 171 fragments of which 116 (67.83%) were polymorphic and 5.47% were rare alleles. A total of 171 alleles with 8.14 alleles per marker were identified and the average polymorphism information content (PIC) value was 0.28. Based on the Jaccard's similarity coefficient the UPGMA dendrogram differentiated all the 42 accessions, with genetic similarity estimates ranging from 0.59 to 0.98. The model-based Bayesian analysis of population structure using the admixture model grouped the 42 arabica germplasm accessions into two ancestral groups. The diversity and structural analysis of 42 arabica world collections identified 11 arabica diverse germplasm accessions and clearly demonstrated the suitability of SRAP markers for coffee genetic diversity studies. These accessions should be analyzed for agronomic and quality parameters, and the same can be utilized in arabica improvement programs. Further, these accessions need to be conserved to enrich arabica diversity.